Actualización del plan de manejo ambiental de la empresa Siderúrgica Ecuatoriana S.A. Quito-Ecuador - Estrella Proaño, Mónica Patricia (2011)
The Environmental Management Plan for the industries, is a tool that serves to prevent, control and mitigate the environmental impacts caused by their production processes. The update of the Environmental Management Plan for the Siderúrgica Ecuatoriana SA Company was made to identify and mitigate the environmental impacts caused by the use of several methods. In the Environmental Management Plan, environmental strategies and activities were designed and improved, according to the company reality and coherent with Ecuadorian legislation. For the implementation of the Plan it is necessary to have the support of the Management, above all for the economic investment mentioned in the Plan and achieve the sustainable development of the company.